Optimum Combination of Food Crops and Livestock Farms as a Strategy to Maximize Farmers' Income in Kupang Regency– Indonesia - Matheos Filipus Lalus; Maria Krova; Maria Rosdiana Deno Ratu (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
Dry land farming in Kupang Regency consists of a combination of food crops farming and horticulture like corn, rice, beans and tubers with livestock such as cattle, pigs, goats and local chickens. Those farms were carried out in a traditional combination heritantly using simple technology and subsistence. The research purpose were to analyze the combination of various types of crops cultivated and types of livestock raised by the farmers in order to achieve maximum income and to analyze the contribution of various types of food crops and horticulture and types of livestock to increase the farmers’ income. The data were analyzed by applying a simplex algorithm approach. The results showed that the optimum combination of resources that generate maximum income was IDR 47,646,888.86. Contributions of various farms were as follow: food crops and horticulture including rice (X1) of  IDR 2,115,984.17; corn (X2) of  IDR. 754.840.28; peanuts (X3) of  IDR 184,970.33; and sweet potatoes (X4) of IDR 1,432,994.17. Then, the contribution of livestock likes : cattle (X5) reached at IDR 2,689,130.43; goats (X6) at IDR 1,098,571.43; pigs (X7) IDR 58,851.35 and chickens (X8) IDR 293.310.81; and off-farm activities (X9) at IDR 262,458.3